Resiliensi dan Ide Bunuh Diri Pada Penderita Human Immunodeficiency Virus (HIV) - Ari Kresna Dewi, Ni Luh Gede; Candra, I Wayan; Sumirta, I Nengah; Harini, I Gusti Ayu; Putri Rukmini, Ni Kadek (Jurnal Gema Keperawatan, 2025)
Stigma, discrimination and changes in health conditions experienced by HIV sufferers can have serious impacts on the psychological condition of sufferers, including increasing suicidal ideation which can be triggered by feelings of hopelessness, depression, and lack of social support. Resilience is known to play a role in reducing individual stress levels and reducing the death rate from suicide. The purpose of this study was to determine the relationship between resilience and suicidal ideation in HIV. This type of research is quantitative research with a correlational analytical method and uses a cross-sectional approach. The research sample consisted of 116 HIV sufferers selected using a purposive sampling technique. Data were collected using the Connor-Davidson Resilience Scale (CD-RISC) questionnaire and The Suicide Behaviors Questionnaire-Revised (SBQ-R). The statistical test technique used was the Spearman's Rank Test. The results showed that the majority of HIV sufferers' resilience was in the high category of 75 respondents (64,7%) and low suicidal ideation of 85 respondents (73,3%). There is a significant relationship between resilience and suicidal ideation in HIV sufferers (p = 0,000 alpha 0,05) with a moderate strength of relationship between the two variables and a negative nature or direction of the relationship, meaning that the higher the resilience of HIV sufferers, the lower the suicidal ideation in HIV sufferers.